Glass slipper, gold sandal : a worldwide Cinderella - Fleischman, Paul.; Paschkis, Julie, 1957- (New York : Henry Holt and Co., 2007)
The author draws from a variety of folk traditions to put together this version of Cinderella, including elements from Mexico, Iran, Korea, Russia, Appalachia, and more.
Maps on lining papers.
Notable Social Studies Trade Books for Young People, 2008.
Keywords: Folklore; Folklore; Folklore